Hidden sides of the credit economy: Emotions, outsourcing, and Indian call centers. (June 2013) - Poster, Winifred R
Engaging in credit is not necessarily a rational activity for consumers. Firms utilize sociological resources and techniques to convince them to sign on to credit accounts, maintain their purchasing habits, and pay on their debts. This analysis examines how global credit industries, their subcontracting firms, and their employees, carry this out. Focusing on Indian call centers, where Indian employees provide customer service for US consumers, this study reveals three hidden and inter-related dynamics of credit. First, emotions are integral to the credit industry. It relies on frontline labor, emotion workers who communicate directly with the consuming public. To secure credit, these employees learn and utilize strategies that appeal to customers' intimacies (deep sensitivities and anxieties about money, family, self, etc.) and moralities (ethics about finance and sense of honor about paying debts). Second, credit is a driver of outsourcing. This industry has historically been the founder of, and continues to be, the primary client base for, offshore customer services in India. Third, outsourcing facilitates the emotional components of credit work. Moving these functions from the Global North to South enables credit firms to access highly skilled and inexpensive workers, and monitor their emotions rigorously in the ongoing labor process. This represents globalization of an affect economy, as Northern credit firms use outsourcing to extract emotional labor from the Global South (Hochschild, 2003). These firms face challenges, however, in translating US moralities and intimacies of credit to India, revealing a transnational cognitive dissonance in the meanings of credit and consumption.